E-tax system effectiveness in reducing tax evasion in Nigeria - Adegbola Olubukola Otekunrin (LLC "CPC "Business Perspectives", 2021)
This study examined how electronic tax system (E- tax system) reduces tax evasion in Nigeria. The survey sample was drawn from Federal Inland Revenue Service (FIRS) staff and small and medium-scale enterprise taxpayers registered in F.C.T., Abuja, Nigeria. Primary data was derived from a questionnaire administered to a population of 60 officials and employees of the FIRS and taxpayers at a small and medium-scale enterprise registered in F.C.T., Abuja, Nigeria. The secondary data used was extracted from the tax revenue collection report on the FIRS platform for 2000–2019 (20 years). The conclusive research design was used. General linear model and linear regression were used to analyze the data collected. The E-tax system was measured using actual tax revenues and the level of electronic tax services. In contrast, tax evasion was measured using tax compliance and mind-set of taxpayers towards E-tax system. Taxpayers’ attitudes towards E-tax system, actual tax revenue, tax compliance and the level of electronic tax services were used as mediating and control variables; thus, results established a significant relationship, and this relationship is an adverse one. The work shows that an effective electronic tax system will significantly reduce tax evasion. Therefore, the proper implementation of the electronic tax system helps mitigate the problem of tax evasion that causes economic and social detriments in the tax administration system.